Implementasi Sistem Monitoring Jaringan dan Server Menggunakan Nagios Berbasis Linux - Al Islami, Hidayatullah; Irawan, Achmad Ferrysqo; Kusuma, Susanna Dwi Yulianti (Universitas Harapan Medan, 2025)
Advances in information technology require companies to have reliable network and server monitoring systems to ensure service availability. This research aims to implement a monitoring system using Linux-based Nagios at PT. Established to increase efficiency and responsiveness in detecting network and server disruptions. The research methods used include needs analysis, system configuration, as well as testing and evaluating the performance of the system that has been implemented. The research results show that the Nagios implementation is able to provide real-time notification of anomalies that occur, thereby speeding up the troubleshooting process and increasing system reliability. With this system, companies can optimize IT infrastructure management, reduce the potential for downtime, and improve the overall quality of IT services.